Syntax-Based Collocation Extraction - Seretan, Violeta (Text, Speech and Language Technology, 2011)
Collocation is a key language phenomenon which crucially impacts any text production task and which is exploitable in many text analysis tasks. This book offers a comprehensive and up-to-date review of the theoretical and practical work on this topic.